2015
DOI: 10.1681/asn.2014050479
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 Elicits Innate Lymphoid Cells and Multipotent Progenitor Type 2 Cells That Reduce Renal Ischemic/Reperfusion Injury

Abstract: IL-25 is an important immune regulator that can promote Th2 immune response-dependent immunity, inflammation, and tissue repair in asthma, intestinal infection, and autoimmune diseases. In this study, we examined the effects of IL-25 in renal ischemic/reperfusion injury (IRI). Treating IRI mice with IL-25 significantly improved renal function and reduced renal injury. Furthermore, IL-25 treatment increased the levels of IL-4, IL-5, and IL-13 in serum and kidney and promoted induction of alternatively activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…IL-25 also sustains homeostasis and activation of IL-13-producing ILC2 and type II natural killer T (NKT) cells in adipose tissue (17). Increasing adipose tissue levels of IL-13-producing ILC2 and type II NKT cells by adoptive transfer or IL-25 administration can increase adipose eosinophil and M2-like macrophage levels (17,18). Thus, a newly defined ILC2-eosinophil-M2 axis maintains adipose tissue metabolic homeostasis.…”
Section: Maintenance Of Normal Adipose Tissue Functionmentioning
confidence: 99%
“…IL-25 also sustains homeostasis and activation of IL-13-producing ILC2 and type II natural killer T (NKT) cells in adipose tissue (17). Increasing adipose tissue levels of IL-13-producing ILC2 and type II NKT cells by adoptive transfer or IL-25 administration can increase adipose eosinophil and M2-like macrophage levels (17,18). Thus, a newly defined ILC2-eosinophil-M2 axis maintains adipose tissue metabolic homeostasis.…”
Section: Maintenance Of Normal Adipose Tissue Functionmentioning
confidence: 99%
“…The M2 phenotype can be induced ex vivo or in vivo via IL‐10 and transforming growth factor (TGF)‐β stimulation for treating kidney diseases . The type 2 innate lymphoid cells (ILC2s), which are a recently described innate immune cell population that can be activated by IL‐33 or IL‐25, also contribute to M2 polarization of macrophages through secretion of various type 2 cytokines, such as IL‐4 and IL‐13 …”
Section: Introductionmentioning
confidence: 99%
“…In the seminal study reported by Huang et al , it was demonstrated that IL‐25–dependent inflammatory ILC2s also express high levels of GATA‐3 (more than that expressed by natural ILC2s), and that they express an intermediate amount of retinoic acid receptor–related orphan nuclear receptor γt (RORγt) (a smaller amount than that expressed by ILC3s, but significantly distinct from the amount expressed by natural ILC2s). The exact contribution of these different transcription factors in modulating ILC2 expansion needs to be better clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, IL‐25 regulates the development of autoimmune inflammation mediated by IL‐17–producing T cells . Furthermore, IL‐25/IL‐17RB activation promotes Th2 responses by increasing the frequency of M2‐type macrophages and the differentiation of both natural and inflammatory group 2 innate lymphoid cells (ILC2s) . Despite these pivotal functions in modulating immune responses, the roles of the IL‐25/IL‐17RB axis and of ILC2s in the pathogenesis of experimental SS and primary SS, as well as in primary SS–associated lymphoma, have not yet been investigated.…”
mentioning
confidence: 99%